2021
DOI: 10.1093/ajcn/nqaa445
|View full text |Cite|
|
Sign up to set email alerts
|

Growth, body composition, and cardiovascular and nutritional risk of 5- to 10-y-old children consuming vegetarian, vegan, or omnivore diets

Abstract: Background Plant-based diets (PBDs) are increasingly recommended for human and planetary health. However, comprehensive evidence on the health effects of PBDs in children remains incomplete, particularly in vegans. Objectives To quantify differences in body composition, cardiovascular risk, and micronutrient status of vegetarian and vegan children relative to omnivores and to estimate prevalence of abnormal micronutrient and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
82
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(135 citation statements)
references
References 46 publications
9
82
2
4
Order By: Relevance
“…In contrast to a recent study [ 14 ], there was no elevated risk for iron deficiency in the vegetarian or vegan subgroup. Obviously, the higher iron intake observed in the vegan participants of the VeChi Youth Study could compensate for the lower bioavailability of non-haem iron in plant-based diets (average iron bioavailability is 5–12% in a vegetarian diet, 14–18% in a mixed diet) [ 56 , 57 ].…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In contrast to a recent study [ 14 ], there was no elevated risk for iron deficiency in the vegetarian or vegan subgroup. Obviously, the higher iron intake observed in the vegan participants of the VeChi Youth Study could compensate for the lower bioavailability of non-haem iron in plant-based diets (average iron bioavailability is 5–12% in a vegetarian diet, 14–18% in a mixed diet) [ 56 , 57 ].…”
Section: Discussioncontrasting
confidence: 99%
“…However, the prevalence of low concentrations was high, as in representative studies in Germany [ 47 ], partly because in Germany, unlike for example in the USA [ 6 ], supplementation is not recommended for children even with low vitamin D intakes. The aforementioned Polish study confirmed the relevance of vitamin D supplementation in children consuming plant-based diets [ 14 ]. However, vitamin D is strongly associated with calcium absorption and metabolism.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations